Good intentions and perverse effects: the limits of institutional reformism in Colombia and Venezuela - Bejarano, Ana María (2016)
During the 1990s, in order to manage the crisis of democracy. Venezuela and Colombia carried out institutional reforms which were aimed at improving the decentralization process, the electoral systems and the Constitution; at first sight. however, it seems that the outcomes coming from such reforms have deepened the crises. With regard to this paradoxical situation, the author argues that any reform process causes unintended and unpredictable consequences, some of which could not be always beneficial. Since there are always costs associated to institutional reform, it is necessary to avoid those kind of diagnosis which are prone to see reality as an uncontested truth.